(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article will help us to understand Emotional Knowledge and Emotional Abstract Emotional knowledge and emotional intelligence (EI) are closely related yet distinct concepts that play a crucial role in human interactions, decision-making, and overall well-being. Emotional knowledge refers to understanding emotions, their causes, and their consequences, while emotional intelligence involves the ability to recognize, regulate, and use emotions effectively. This paper explores the relationship between these two constructs, their development, and their significance in personal and professional life. Additionally, the article provides strategies for enhancing emotional knowledge and emotional intelligence and examines cultural and individual differences in emotional processing.